EFFECTS OF GENDER MODERATION: LOCUS OF CONTROL, ORGANIZATIONAL BEHAVIOR, BUDGET PLANNING, EMPLOYEE PERFORMANCE - Mareta, Yesi Restia; Martika Sari, Yetri; Devi, Yulistia (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
The purpose of this study is to analyze how the performance of employees in the organizational bureau of the Lampung Provincial Regional Secretariat, in order to improve their performance, is influenced by individual beliefs, both internal and external, cooperation and responsibility. The research data was collected using a questionnaire and obtained from 42 respondents who are employees at the Lampung Provincial Regional Secretariat Organization Bureau. This study uses a quantitative approach of primary data with research instruments using the questionnaire method, namely distributing questionnaires, then the results are collected and analyzed using SEM-PLS analysis with SmartPLS 3 software. The study results showed that locus of control did not affect employee performance, organizational behavior did not affect employee performance, and budget planning affected employee performance in the Lampung Provincial Regional Secretariat Organizational Bureau. Then, the gender moderation test, which aims to understand if and how gender differences influence the relationship between locus of control, organizational behavior, and budget planning to employee performance, found that gender does not play a significant role in these relationships. The realization of a budget plan must be determined by something other than the difference between men and women in the organizational bureau of the Lampung provincial regional secretariat.